PEMBINAAN KAMPUNG MODERASI BERAGAMA MELALUI SOSIALISASI TANAM KEBERSAMAAN PANEN KEMAKMURAN DI DESA TAWANG KECAMATAN WATES KABUPATEN KEDIRI - Huda, M. Thoriqul; Abdillah, Naufal Hasan; Sulton, Habib Sana Budin; Nasor, Azizi Saifun; Wulandari, Putri; Putri, Ayu Septiana; Firdaus, Erina Dita (LP2M Institut Agama Islam Ngawi, 2025)
Religious moderation is a way to strengthen relations between religious communities. Forming cooperation and strengthening communication is the most important thing in the process of establishing religious moderation in society. Apart from that, society needs to foster harmony and tolerance to avoid prolonged conflict. By implementing these things, religious people in society can carry out their religious activities safely without worrying about disapproval and rebellion from other religions. Because of this, it is necessary to hold socialization activities in the community regarding the essence of religious moderation and how religious moderation is a way to foster prosperity in society. This then became the reason for the formation of the